Motor learning through induced variability at the task goal and execution redundancy levels - Ranganathan, R.; Newell, K. M. (Journal of Motor Behavior, 2010)
The authors examined the influence of introducing variability at two different levels in the learning of a striking task. Variability at the task goal level was introduced by changing target location, whereas variability at the execution redundancy level was introduced by using an intermediate target that constrained participants to use different paths from trial to trial to strike the same target. After practice, participants were transferred to 2 test conditions: (a) a fixed-target test, where the position of the target was unchanged; and (b) a variable-target test, where the position of the target was varied from trial to trial. The results from the manipulation at the task goal level were consistent with predictions from the specificity of practice hypothesis. In both the fixed- and variable-target tests, the best performance was achieved by the group that had practiced in the condition matching the test condition. At the execution-redundancy level, practicing multiple solutions to achieve the task goal did not improve performance in either the fixed- or variable-target tests. These results show that introducing variability at the task goal and execution redundancy levels has different effects on learning and generalization and that practice schedules that constrain the participant to use redundant solutions may not facilitate learning.